2014
DOI: 10.3382/ps.2014-03959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various sources and levels of iodine, as well as the kind of diet, on the performance of young laying hens, iodine accumulation in eggs, egg characteristics, and morphotic and biochemical indices in blood

Abstract: Young hens were fed over a period of 150 d with 2 kinds of diets including corn and soybean meal or corn, soybean, and rapeseed meal. Diets were enriched with potassium iodide (KI) or potassium iodate (KIO3) as an I source in amounts equal to 1, 3, or 5 mg of supplemented I/kg of feed. The hen performance, egg quality, hematological and morphotic indices in blood, hepatic enzyme activity, lipid indices in blood serum as well as I accumulation in wet egg content were determined. Introduction of 00-variety rapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
3
20
3
Order By: Relevance
“…Słupczyńska, Jamroz, Orda, and Wiliczkiewicz () conducted a research on Hy‐Line Brown laying hens over 3 and 5 months of periods. Their results demonstrated that the highest laying rate was observed in group receiving 3 mg of I/kg diet given as KIO 3 ( p = .009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Słupczyńska, Jamroz, Orda, and Wiliczkiewicz () conducted a research on Hy‐Line Brown laying hens over 3 and 5 months of periods. Their results demonstrated that the highest laying rate was observed in group receiving 3 mg of I/kg diet given as KIO 3 ( p = .009).…”
Section: Discussionmentioning
confidence: 99%
“…Słupczyńska et al. () reported that dietary I supplementation (1, 3 and 5 mg/kg as KI or KIO 3 ) did not significantly affect egg yolk, albumen and eggshell percentages over 3‐month experiment but increased albumen ratio after 5 months ( p = .012) and yolk colour after 3 months of experiment ( p = .003).…”
Section: Discussionmentioning
confidence: 99%
“…e effectiveness of such methods is usually expressed as the level of inclusion of an ingredient in a product of animal origin [5,10]. erefore, in the feed industry and among breeders, there is an increasing interest in the possibility of using new materials such as algae enriched in microcomponents [11], fossil materials [12], food industry waste such as yeast [13], and other organic waste [5].…”
Section: Enrichment Of Eggs Withmentioning
confidence: 99%
“…erefore, in the feed industry and among breeders, there is an increasing interest in the possibility of using new materials such as algae enriched in microcomponents [11], fossil materials [12], food industry waste such as yeast [13], and other organic waste [5]. e appropriate content of macro-and microelements in compound feed is also necessary from the point of view of production economics because it will not only allow obtaining products with an increased content of these ingredients but also help to maintain the health and production parameters of animals at an optimal level [14].…”
Section: Enrichment Of Eggs Withmentioning
confidence: 99%
See 1 more Smart Citation